The role of headmasters of rural schools in attaining high UPSR achievement, Malaysia: teachers perspectives - Abd Razak Al-Hafiz, Afareez; Salleh, Mohamad Johdi (Center for Enhancing Knowledge, United Kingdom, 2012)
The foremost purpose of this study is to examine the role of the headmaster of rural schools as perceived by teachers, in attaining pupils’ high academic achievement, particularly in the UPSR - Ujian Pencapaian Sekolah Rendah or PSAT - Sixth Year Primary School Achievement Test). The samples are consisted of two hundred teachers from twenty selected rural excellent primary schools in the State of Johor Malaysia who participated in the study as respondents. The researcher employed the mix-method approach, which is a combination of both quantitative and qualitative approaches to accumulate data through questionnaires and interviews. The study reveals that, the teachers perceived their headmasters executed their roles remarkably well in contributing to the success of pupils in the UPSR examination through the coordination of various factors even with the lack of resources and exposure. Based on the findings, the researcher recommends that the headmasters make full use of the authority entrusted upon them to come up with new ideas to cope with the rapid changes of the educational field; construct conducive, organized, and disciplined learning and teaching environment; acquire benefits from the resources; and be prepared with systematic planning.